Seasonal variations of cauda epididymal spermatozoa of bucks - Swain, Dilip Kumar; Yadav, Sarvajeet; Pandey, Vijay (Journal of Advanced Veterinary and Animal Research, 2016)
Objective: The study was conducted to evaluate the influence of season on cauda epididymal spermatozoa isolated from bucks. Materials and methods: Testes of 30 mature bucks were collected from local slaughter house, and were processed for the retrieval of cauda epididymal spermatozoa for evaluation. Testes were collected in three seasons (winter, summer and rainy), and each season was having 10 pairs of testicles. Recovered spermatozoa from the cauda epididymis were processed immediately for evaluation of semen attributes (Spermatozoa motility, viability, plasma membrane integrity, acrosomal status and DNA integrity). Results: Physiological effect of season was observed on progressive motility, percent of live spermatozoa, spermatozoal membrane integrity (HOST), acrosomal integrity, capacitation status and DNA integrity. Progressive motility, percent live spermatozoa, HOST positive spermatozoa, were found significantly (P<0.05) high in summer season, whereas, significantly (P<0.05) lower comet positive spermatozoa were found in summer season as compared to rainy and winter. Compromised acrosomal status was seen in winter and rainy seasons as compared to summer. Conclusion: Compromised acrosome along with plasma membrane and higher percentage of spermatozoa with damaged DNA in cauda spermatozoa were observed during winter and rainy seasons as compared to summer season. Summer season was found to be the most suitable season for collection of cauda epididymal spermatozoa and can effectively be used for assisted reproduction with further investigations of associated mechanisms. http://doi.org/10.5455/javar.2016.c155